miR-224-5p Attenuates Allergic Responses in Mice with Allergic Rhinitis by Modulating the Th1/Th2 Response - Yuxiao Li; Ran An; Mingjin Wu; Jiayan He; Xiaoguang He (Analytical Cellular Pathology)
Background. Allergic rhinitis (AR) is a common chronic respiratory disease that has become a global health problem. miRNAs play an important role in multiple immune and inflammatory diseases, including AR. In this work, the mechanism by which miR-224-5p regulates AR in vivo and in vitro was examined. Methods. Human nasal epithelial cells (HNEpCs) were used to establish an AR cell model induced by Der P1, and C57BL/6 mice were used to establish an AR animal model induced by OVA (ovalbumin). RT-qPCR was used to determine the level of miR-224-5p; western blot analysis was used to determine GATA3; ELISA was used to determine the levels of OVA-specific IgE, IFN-γ, IL-4, IL-5, and IL-13; flow cytometry was used to determine the differentiation of Th1 and Th2 cells; and HE and PAS staining was used to observe the histopathological alterations in the mouse nasal mucosa and spleen. Results. miR-224-5p was downregulated in nasal mucosa from mice with AR and an AR cell model. Overexpressed miR-224-5p can improve AR development and attenuate AR symptoms by regulating GATA3-mediated Th1/Th2 responses. Conclusion. miR-224-5p attenuates allergic reactions in mice with AR by regulating the Th1/Th2 response.